Harmonização orofacial: Análise do conhecimento dos cirurgiões-dentistas sobre os riscos clínicos e aspectos legais e éticos na prática da rinomodelação e bichectomia - Rodrigues, Lívia Graziele (2021)
Dentistry has proved to be a complex science that treats the patient holistically, restoring the masticatory functions and the aesthetics expected for a natural smile. However, when permeating the field of facial aesthetics, many dentist have been carrying out various procedures, which are considered controversial according to dental practice. Orofacial harmonization consists of making of a patient's face more aesthetically proportional through procedures such as: facial filling with biomaterials, application of botulinum toxin, bichectomy, cervical lipoplasty and rhinomodeling. The objective of this study is to evaluate the perception of dentists regarding the technical capacity to perform rhinomodeling and bichectomy procedures regarding the legal support for their performance. After approval by the ethics committee, a self-administered structured questionnaire with 16 questions about the participant's profile, orofacial harmonization topics and specific subjects on bichectomy and rhinomodeling was applied to the professionals who were willing to participate. Of the 180 questionnaires answered, 105 (58.3%) were from female professionals, 41 (22.9%) said they performed orofacial harmonization procedures in their clinical routine. Asked about feeling able to treat an already installed nasal necrosis, 19 (11.0%) participants declared to be qualified to proceed with this type of treatment, while 110 (72.8%) of them informed that they would forward this case of complication to a Doctor. It was possible to perceive that, in general, the professionals are not aware of the norms that support them regarding the performance of new procedures included in the list that Dentistry already practices, in addition, even among the professionals who attended training courses in Orofacial Harmonization, most of them do not feel prepared to perform procedures such as rhinomodeling and treat complications resulting from bichectomy surgery.